Penyelesaian Capacitated Vehicle Routing Problem (CVRP) dengan Nearest Neighbour (Studi Kasus: Russian CVRP Instances) - Sanggala, Ekra; Bisma, Muhammad Ardhya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Capacitated Vehicle Routing Problem (CVRP) is one of the most popular VRP variants. Nearest Neighbour (NN) is a very simple and very easy heuristic. The basic concept of Nearest Neighbour is to choose the closest point that has never been visited. Russian CVRP Instances created by the author based on Russian history and places in Russia. The total route length for each CVRP Instance is AK-47-CVRP (60857 km), Gagarin-108-CVRP (75920 km), Mendeleev-101-CVRP (116248 km), Petersburg-182-CVRP (2713 km), Popov-250-CVRP (164974 km), Russia-10-Nodes-CVRP (15911 km), Russia-20-Nodes-CVRP (21480 km), Siege-of-Leningrad-872-CVRP (11012 km), World-Cup-Stadium-12-CVRP (10793 km) and Yashin-270-CVRP (105616 km).